2016
DOI: 10.1038/nature19063
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic enantioselective 1,6-conjugate additions of propargyl and allyl groups

Abstract: Conjugate (or 1,4-) additions of carbanionic species to α,β-unsaturated carbonyl compounds are vital to research in organic and medicinal chemistry, and there are several known chiral catalysts that facilitate the catalytic enantioselective additions of nucleophiles to enoates1. However, catalytic enantioselective 1,6-conjugate additions are uncommon, and ones that are able to incorporate readily functionalizable moieties, such as propargyl or allyl groups, into acyclic α,β,γ,δ-doubly unsaturated acceptors are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
50
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(51 citation statements)
references
References 32 publications
1
50
0
Order By: Relevance
“…[6] Under these reaction conditions,p roducts derived from chainwalking isomerization are observed, [6b] restricting access to anarrow range of product classes. [7] Thelack of generality in Z-selective diene additions highlights the difficulty in controlling both site-and stereoselectivity in catalytic diene functionalization, [8] particularly in those reactions that generate thermodynamically less favorable product isomers. [9] From am echanistic perspective,i mproving reductive chemoselectivity while inhibiting chain-walking events in diene-aldehyde coupling can potentially be realized by tailoring the reactivity of the Rh intermediates involved in the reaction pathway.Specifically,ifboth diene insertion into the Rh-hydride catalyst and electrophilic capture of the resultant Rh-allyl outpace undesirable isomerization, bhydride elimination, or other reductive processes,adirect and selective coupling process should be possible.Werecently reported that formic acid acts as reducing agent for the Zselective 1,6-reduction of dienyl esters [10] and questioned whether this pathway could be diverted to enable reductive coupling.F ormic acid has been used as areductant for metalcatalyzed CÀCb ond-forming carbonyl allylation and vinylation processes.…”
Section: Introductionmentioning
confidence: 99%
“…[6] Under these reaction conditions,p roducts derived from chainwalking isomerization are observed, [6b] restricting access to anarrow range of product classes. [7] Thelack of generality in Z-selective diene additions highlights the difficulty in controlling both site-and stereoselectivity in catalytic diene functionalization, [8] particularly in those reactions that generate thermodynamically less favorable product isomers. [9] From am echanistic perspective,i mproving reductive chemoselectivity while inhibiting chain-walking events in diene-aldehyde coupling can potentially be realized by tailoring the reactivity of the Rh intermediates involved in the reaction pathway.Specifically,ifboth diene insertion into the Rh-hydride catalyst and electrophilic capture of the resultant Rh-allyl outpace undesirable isomerization, bhydride elimination, or other reductive processes,adirect and selective coupling process should be possible.Werecently reported that formic acid acts as reducing agent for the Zselective 1,6-reduction of dienyl esters [10] and questioned whether this pathway could be diverted to enable reductive coupling.F ormic acid has been used as areductant for metalcatalyzed CÀCb ond-forming carbonyl allylation and vinylation processes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Hoveyda et al reported a PLE‐mediated diastereoselective desymmetrization of a chiral malonate diester . To the best of our knowledge, there are no published reports of PLE‐catalyzed hydrolysis of malonate diesters with a preexisting chiral center and a phthalimide group.…”
Section: Resultsmentioning
confidence: 99%
“…All the reagents used were of analytical grade without further purification. Oxoindole-derived methide derivatives was obtained following the literature [12].…”
Section: General Informationmentioning
confidence: 99%
“…In this regard, the 1,6-conjugated addition reaction catalyzed by Brønsted acids or Lewis acids for new chemical bond formation can provide a variety of bioactive compounds, and has complete atom economy [11]. Thus, the 1,6-conjugated addition reaction is attracting much research interest in academia [12][13][14].…”
Section: Introductionmentioning
confidence: 99%